(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The current study has aimed to determine the importance of strategic thinking (organizational perception, assumption leadership, time thinking, strategic thinking, organizational perception, assumption leadership, thinking time, smart opportunities) (The field of growth and educational activities, the financial field, the field of marketing index, the field of operations and activities in the internal environment), to clarify the impact of strategic thinking on outstanding university performance through the strategy of evaluating the performance of human resources "The researcher used the descriptive approach in the form of a survey to suit the nature and objectives of the study." The study was attended by (100) employees and employees of the University of Al-Qasim Al-Khadraa as they responded to the strategic thinking scale and the distinguished university performance measure. (SPSS) The researcher reached a number of results. The results were the correct choice for the institution to get out of the problems and crises that it faces in its work through strategic thinking that gives comprehensiveness in the development of the university performance and puts the correct assumptions in time to seize opportunities Available to the Organization to achieve the strategic goals. There is a variation in the university’s adoption of strategic thinking practices. The results of the study show that there is a concern by the university administration about Teams and contribute to the activities of the university and participate in its scientific and community activities, which contributes to the collective participation by the members of the study sample in the decisions, which enhances the work behavior and outstanding performance.